Numerical optimization of hole making in GFRP composite using abrasive water jet machining process - Ibraheem, Hussein Mohammed Ali; Iqbal, Asif; Hashemipour, Majid (Chinese Inst Engineers, 2015)
Machining of composite materials for the production of bolt holes is essential in the assembly of the structural frames in many industrial applications of glass fiber-reinforced plastic (GFRP). Abrasive water jet cutting technology has been used in industry for such purposes. This technology has procured many overlapping applications and as the life of the joint in the assembled structure can be critically affected by the quality of the holes, so it is important for the industry to understand the application of the abrasive water jet cutting process on GFRP composite materials. The aim of the present work is to assess the influence of abrasive water jet machining parameters on the hole making process of woven-laminated GFRP material and to find the optimum values of the process parameters. Statistical approach was used to understand the effects of the predicted variables on the response variables. Analysis of variance was performed to isolate the effects of the parameters affecting the hole making in abrasive water jet cutting. The results show that the optimum values of cutting feed, fiber density, water jet pressure, standoff distance, and abrasive flow rate upon the response variables are 0.3m/min, 0.82g/cm(3), 150MPa, 2mm, and 100g/min, respectively.
Keywords: abrasive water jet cutting; hole making; laminated glass fiber reinforced plastic; optimization